Addison's theater of the aesthetic - Taylor, DF (Johns Hopkins University Press, 2021)
This essay considers how far Joseph Addison found the theater to be especially equipped in formal and material terms for theorizing the aesthetic. It argues for the significance of his 1707 opera Rosamond as an experimental drama that uses the manifold resources of the stage as the materials through which to grapple conceptually with the aesthetic in ways that depart from the insights of Addison's 1712 essay on the "Pleasure of the Imagination"--an essay that programmatically avoids discussion of the theater. In particular, this essay argues that Rosamond calls into question not only the binaries between showing and telling, seeing and reading, so forcefully rehearsed in Addison's critical essays, but more fundamentally his distinction between imagination's primary and secondary pleasures.